Les valeurs de travail et les intérêts professionnels des élèves inscrits au programme d’insertion sociale et professionnelle - Marceau, Denis; Gingras, Marcelle; Boulanger, Rachel (Canadian Journal of Counselling and Psychotherapy, 2007)
This article examines work values and professional interests of students following a programme named Insertion sociale et professionnelle (ISP) in Eastern Townships during 1989-90. These characteristics are respectively measured by the Questionnaire de valeurs de travail (QVT) developed by Perron (1986) and the Test visuel d'intérêts (TVl) developed by Tétreau and Trahan (Ì986). The results indicate that those students had not a different work values profile than other students in general or vocational education, that girls had higher score on Climate scale and boys on Risk scale, and there is no difference when we considered learning difficulties variable. Our results also indicate that vocational interests of these students are relatively different from students in general education but more equivalent of vocational interests of students in vocational education. We also found significant differences between girls and boys on vocational interests: the boys had higher scores on R scale and their profile is RIAECS; girls had higher scores on Social, Artistic, Conventional and Enterprising scales and their profile is SACEIR. A few significant differences were found between students with higher learning difficulties and those with lower learning difficulties. Finally, we found no significant relationship between work values and vocational interests of those students.